Retiring the generation gap how employees young and old can find common ground - Deal, Jennifer J. (Wiley, 2007)
"Written in a highly accessible (and often witty) style, this groundbreaking book addresses a number of generational issues. Deal provides a description of each issue, a summary of the relevant research results, a principle that can be applied to resolve (or at least mitigate) the issue, and practical advice for applying the principle in the workplace. Applying these principles will help everyone to work with, work for, attract, manage, retain, and develop leaders of all generations"--Resource description page
Includes bibliographical references (pages 237-240) and index. - Print version record
Keywords: Work; Conflict of generations; Intergenerational relations; Psychology, Industrial; Travail; Conflit de générations; Relations entre générations; Psychologie du travail; labor; BUSINESS & ECONOMICS; Motivational; BUSINESS & ECONOMICS; Mentoring & Coaching